Pengaruh Adverse Selection Dan Negative Framing Terhadap Eskalasi Komitmen Dalam Pengambilan Keputusan Investasi - Siti Zakiyah Hayati Nasution; Rindah Febriana Suryawati (IPB University, 2019)
Escalation of commitment behavior in investment decision making is an ineffective action by persisting on a project that indicates failure. This study aims to examine whether or not an adverse selection and negative framing effect on the tendency of escalation of commitment. This experimental research uses a 2 x 2 factorial design with an instruments of